Understanding Preventable Deaths in the Geriatric Trauma Population: Analysis of 3, 452, 339 Patients From the Center of Medicare and Medicaid Services Database. Issue 4 (April 2022) - Ang, Darwin; Nieto, Kenny; Sutherland, Mason; O'Brien, Megan; Liu, Huazhi; Elkbuli, Adel
Background: Patient safety indicators (PSIs) are avoidable complications that can impact outcomes. Geriatric patients have a higher mortality than younger patients with similar injuries, and understanding the etiology may help reduce mortality. We aim to estimate preventable geriatric trauma mortality in the United States and identify PSIs associated with increased preventable mortality. Methods: A retrospective cohort study of patients aged ≥65 years, in the CMS database, 2017-second quarter of 2020. Risk-adjusted multivariable regression was performed to calculate observed-to-expected (O/E) mortality ratios for failure-to-prevent and failure-to-rescue PSIs with significance defined as P < .05. Results: 3 452 339 geriatric patients were analyzed. Patients aged 75-84 years had 33% higher odds of preventable mortality (adjusted odds ratio [aOR] = 1.33 and 95% confidence interval [CI] = 1.31, 1.36), whereas patients aged ≥85 years had 91% higher odds of preventable mortality (aOR = 1.91 and 95% CI = 1.87, 1.94) compared to patients aged 65-74 years. Failure-to-prevent O/E were >1 for all PSIs evaluated with central line–related blood stream infection having a high O/E (747.93). Failure-to-rescue O/E were >1 for 10/11 (91%) PSIs with physiologic and metabolic derangements having the highest O/E (5.98). United States' states with higher quantities of geriatric trauma patients experienced reduced preventable mortality. Conclusion: Odds of preventable mortality increases with age. Perioperative venous thrombotic events, hemorrhage or hematoma, and postoperative physiologic/metabolic derangements produce significant preventable mortalities. United States' states differ in their failure-to-prevent and failure-to-rescue PSIs. Utilization of national guidelines, minimization of central venous catheter use, addressing polypharmacy especially anticoagulation, ensuring operative and procedure-based competencies, and greater incorporation of inpatient geriatricians may serve to reduce preventable mortality in elderly trauma patients.